La menace sans visage : Images de l’ennemi dans la presse britannique à la suite des attentats du 11 septembre 2001 - Pascale Villate-Compton (Revue LISA)
When President Bush, along with most of the English speaking media, talked about “war” in the aftermath of the World Trade Center attacks on 9/11/2001, he opened up the way for an array of representations of a multi-faceted enemy, which soon became a focus for fear. Any conflict carries with it the temptation to simplify. Despite repeated warnings against equating terrorists with the Muslim population, some sections of the British press have tended to generalise and to foster irrational fears. The cartoons and photographs of the daily British press in the three months after the attacks show that, often, beyond the precise identification of a culprit, the Other (the foreigner marked by a difference, the Muslim and his religious and cultural practices) ends up representing the enemy. Similarly, any extremist, from Osama Bin Laden to the imam of Finsbury Park mosque in London, becomes the spokesman for the entire Muslim community, a community that is silent and yet suspect.